2018
DOI: 10.1021/acs.inorgchem.8b00697
|View full text |Cite
|
Sign up to set email alerts
|

Computational Prediction and Experimental Realization of p-Type Carriers in the Wide-Band-Gap Oxide SrZn1–xLixO2

Abstract: It is challenging to achieve p-type doping of zinc oxides (ZnO), which are of interest as transparent conductors in optoelectronics. A ZnO-related ternary compound, SrZnO, was investigated as a potential host for p-type conductivity. First-principles investigations were used to select from a range of candidate dopants the substitution of Li for Zn as a stable, potentially p-type, doping mechanism in SrZnO. Subsequently, single-phase bulk samples of a new p-type-doped oxide, SrZnLi O (0 < x < 0.06), were prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Raman spectroscopy governs the inelastic interactions of photons with molecular vibrations or phonons, which is a very efficient way to visualize the local structure of compound. The spectrum for undoped SrZnO 2 matches to a good extent with spectrum reported by Tzitzeklis et al [14] Upon Dy inclusion into the host system, there is noticeable change in peak intensities in Figure 1c. The signals at %123 and 414 cm À1 got diminished with Dy doping, whereas signals at %145 and 178 cm À1 have shown prominent enhancement in intensity.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Raman spectroscopy governs the inelastic interactions of photons with molecular vibrations or phonons, which is a very efficient way to visualize the local structure of compound. The spectrum for undoped SrZnO 2 matches to a good extent with spectrum reported by Tzitzeklis et al [14] Upon Dy inclusion into the host system, there is noticeable change in peak intensities in Figure 1c. The signals at %123 and 414 cm À1 got diminished with Dy doping, whereas signals at %145 and 178 cm À1 have shown prominent enhancement in intensity.…”
Section: Resultssupporting
confidence: 87%
“…Therefore, the nature and concentration of trapping centers can be identified by qualitative and quantitative analysis of glow curves, respectively.SrZnO 2 is a wide bandgap semiconducting material, having direct bandgap of 3.4 eV. [13][14][15] The undoped system exhibits broad band luminescence bestowed by intrinsic defect states present in the forbidden band. [10,[15][16][17] TL study upon gamma irradiation on the undoped SrZnO 2 revealed the existence of glow features in low-and high-temperature regions, which were attributed to shallow and deep intrinsic defects.…”
mentioning
confidence: 99%
“…Density functional theory calculations have also been successfully used to obtain reaction enthalpies for complex oxides with large unit cells and doped oxides from binary oxides, which correctly identied the structures obtained experimentally. [65][66][67] Porous materials nd application in molecular separations, catalysis and sorption. The most industrially widespread microporous inorganic materials are zeolites and zeo-types: crystalline structures formed by XO 4 tetrahedra (where X ¼ Si, Al, P, etc.).…”
Section: Inorganic Materialsmentioning
confidence: 99%
“…Density functional theory calculations have also been successfully used to obtain reaction enthalpies for complex oxides with large unit cells and doped oxides from binary oxides, which correctly identified the structures obtained experimentally. 65–67…”
Section: Materials Synthesismentioning
confidence: 99%